2013
DOI: 10.9790/2402-0318690
|View full text |Cite
|
Sign up to set email alerts
|

Low Concentrations of PCB (Aroclor 1254) Alter Membrane Bound Ion Dependent ATPases in the Hepatocyte Cells of Mice

Abstract: Aroclor 1254, a PCB, notwithstanding its banned status, is still available in the environment in low concentration. Reports on its toxic effects on membrane proteins and the mechanism of actions are rare. Therefore, the present study was conducted to investigate the dose and exposure duration dependent effects of low concentration Aroclor 1254 on total, Na + , K + , Ca ++ and Mg ++ -ATPases on the mouse liver cells. The study tests two hypotheses, (a) the low, environmentally available doses of Aroclor 1254 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Dioxin like chlorinated compounds induce oxidative stress by producing intracellular free radicals and ROS [20] . Oxidative stress caused by reactive oxygen species is also speculated to be pathologically important for various neurodegenerative processes and cognitive deficits [26] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dioxin like chlorinated compounds induce oxidative stress by producing intracellular free radicals and ROS [20] . Oxidative stress caused by reactive oxygen species is also speculated to be pathologically important for various neurodegenerative processes and cognitive deficits [26] .…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that TCDD, in in vivo conditions, generally binds with AhR receptor and targets to blood brain efflux transporter which reduces the accumulation of drug therapeutic agents in neuronal cells [19] . Therefore, the increased intracellular ions are possibly associated with intracellular signaling alteration due to TCDD toxicity [20] . Going through the literature it was observed that studies related to TCDD effects on lysosomal enzyme in brain tissue are rare.…”
Section: Introductionmentioning
confidence: 99%
“…Pathak and Kundu (2013) demonstrated that the renal toxicity attributed to Aroclor is not dose dependent, but the length of exposure is crucial for the production of such adverse effects. Treatments with MeHg and Aroclor in mixture did not cause tubular degeneration, but induced mononuclear infiltration, with the predominance of lymphocytes and glomerular hypercellularity.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these animals, it was observed hyaline casts. Pathak and Kundu (2013) demonstrated that the renal toxicity attributed to Aroclor is not dose dependent, but the length of exposure is crucial for the production of such adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…These organochlorine pollutants are lipophilic and tend to accumulates in adipose tissue so symptoms relevant to toxicity manifest after starvation condition of living organism [32][33][34] . The alterations in the enzyme activities possibly showed cell defense toward incoming ROS which might have formed outside renal cells [35] . *Significance at P = 0.05 (F crit = 5.14)…”
Section: Resultsmentioning
confidence: 99%